Study of Hardness of Superhard Crystals by Topological Indices - Xiujun Zhang; Muhammad Naeem; Abdul Qudair Baig; Manzoor Ahmad Zahid (Journal of Chemistry)
Topological indices give immense information about a molecular structure or chemical structure. The hardness of materials for the indentation can be defined microscopically as the total resistance and effect of chemical bonds in the respective materials. The aim of this paper is to study the hardness of some superhard BCx crystals by means of topological indices, specifically Randić index and atom-bond connectivity index.